CONTEXT–BASED LEARNING WITH GAMIFICATION TO DEVELOP CRITICAL THINKING AND PROBLEM SOLVING SKILLS ON WATER SOURCES AND THEIR UTILIZATION OF PRATHOMSUKSA 5 STUDENTS - Pokong, Tossapon; Chapoo , Suriya (Journal of Graduate School Sakon Nakhon Rajabhat University, 2026)
This research aimed to examine the characteristics and outcomes of integrating context–based learning with gamification to enhance critical thinking and problem–solving skills concerning water sources and utilization. The participants were five Prathomsuksa 5 students from educational opportunity expansion schools located in Phitsanulok Province. The research used a three–cycle action research design. Data collection instruments included instructional lesson plans, reflective journals, critical thinking and problem–solving assessment forms, supplementary activity worksheets, and activity sheets. Data analysis was conducted using content analysis and percentage. The findings were as follows: 1) The context–based learning integrated with gamification consisted of familiarizing learners with the situation; clearly emphasizing objectives, rules, and conditions for receiving rewards; verifying information sources; demonstrating the effective use of keywords for information retrieval; linking information through the use of font size, color coding, or symbols to support categorization, and consistently reviewing instructions for each activity and 2) The development of students’ critical thinking and problem–solving skills were categorized into four elements: (1) effective reasoning, (2) systematic thinking, (3) critical thinking and decision–making, and (4) problem–solving. Overall, most elements showed improved evaluation scores at both the group and individual levels.